Essere "presenza" curante: aver cura dell'esperienza della cura - Cristina Palmieri (University of Bologna, 2014)
Before being a pedagogical and philosophical category, caring is a practice embodied in actions, looks, postures, words. Caring is "presence": according to Heidegger, it is "being-in-the-world-with-the-others". Caring endows situations experienced in healthcare contexts with unique qualities, e.g. when we accompany the dying, or when we allow people who live in existential distress to experiment different opportunities to be themselves. Being a caring presence "is at issue for it": the practitionerslive an inextricable and problematic intertwining between personal and professional dimensions. The article questions how to support this presence from a pedagogical point of view. Self-care, understood as an educational, professional and self-learning practice, could be considered as an answer that allows us to go beyond the individual empowerment. Indeed, self-caring could be an essential condition to take care of the whole existential experience in the healthcare contexts. The very understanding of how this process could work is a question open to further investigation.